2014
DOI: 10.2340/00015555-1840
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar Keratoderma of the Gamborg-Nielsen Type is Caused by Mutations in the SLURP1 Gene and Represents a Variant of Mal de Meleda

Abstract: Palmoplantar keratoderma of the Gamborg-Nielsen type (PPK-GN) is a rare autosomal recessive skin disorder described in patients from Sweden. Mal de Meleda (MDM) is also a rare autosomal recessive inherited PPK first reported in 5 families from the island of Meleda. The 2 conditions phenotypically overlap and are characterised by palmoplantar erythematous hyperkeratotic plaques. The genetic background giving rise to PPK-GN has hitherto been unknown, whereas MDM is known to be caused by mutations in the gene enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 20 publications
(25 reference statements)
1
37
0
1
Order By: Relevance
“…Gruber et al [32] reported an additional homozygous mutation of SLURP-1 that leads to an atypical phenotype wherein the plantar surface is spared. Zhao et al [7] showed that a less severe PPK, which has historically been characterized as a hereditary PPK of the Gamborg-Nielsen type, may, in fact, more accurately be referred to as a variant of Mal de Meleda that is seen in the Swedish population. Of note, the mutation responsible for 14 of the 15 cases in the study by Zhao et al is one that has been previously described in other reports of Mal de Meleda, generally without considerable phenotypic variation [8,34].…”
Section: Genetics and Pathophysiologymentioning
confidence: 98%
See 4 more Smart Citations
“…Gruber et al [32] reported an additional homozygous mutation of SLURP-1 that leads to an atypical phenotype wherein the plantar surface is spared. Zhao et al [7] showed that a less severe PPK, which has historically been characterized as a hereditary PPK of the Gamborg-Nielsen type, may, in fact, more accurately be referred to as a variant of Mal de Meleda that is seen in the Swedish population. Of note, the mutation responsible for 14 of the 15 cases in the study by Zhao et al is one that has been previously described in other reports of Mal de Meleda, generally without considerable phenotypic variation [8,34].…”
Section: Genetics and Pathophysiologymentioning
confidence: 98%
“…Originally, there were three different gene mutations of SLURP-1 identified by Fischer et al: a homozygous single nucleotide deletion, a homozygous point mutation, and a homozygous splice site mutation, suggesting a founder effect from the original cases reported in Croatian and Algerian families. However, as more cases have been reported, at least 14 other mutations have been identified from families in at least 19 other countries [7,34,35]. In addition to the homozygous mutation genotype, there have also been cases showing compound heterozygous mutations with disease phenotype [36].…”
Section: Genetics and Pathophysiologymentioning
confidence: 98%
See 3 more Smart Citations